Do fungi look like macroparasites? Quantifying the patterns and mechanisms of aggregation for host-fungal parasite relationships - Schrock, Sarah A. R.; Walsman, Jason C.; DeMarchi, Joseph; Lesage, Emily H.; Ohmer, Michel E. B.; Rollins-Smith, Louise A.; Briggs, Cheryl J.; Richards-Zawacki, Corinne L.; Woodhams, Douglas C.; Knapp, Roland A.; Smith, Thomas C.; Haddad, Célio F. B. [UNESP]; et al. (The Royal Society, 2025)
Most hosts contain few parasites, whereas few hosts contain many. This pattern, known as aggregation, is well-documented in macroparasites where parasite intensity distribution among hosts affects host-parasite dynamics. Infection intensity also drives fungal disease dynamics, but we lack a basic understanding of host-fungal aggregation patterns, how they compare with macroparasites and if they reflect biological processes. To begin addressing these gaps, we characterized aggregation of the fungal pathogen Batrachochytrium dendrobatidis (Bd) in amphibian hosts. Utilizing the slope of Taylor's Power law, we found Bd intensity distributions were more aggregated than many macroparasites, conforming closely to lognormal distributions. We observed that Bd aggregation patterns are strongly correlated with known biological processes operating in amphibian populations, such as epizoological phase (i.e. invasion, post-invasion and enzootic), and intensity-dependent disease mortality. Using intensity-dependent mathematical models, we found evidence of evolution of host resistance based on aggregation shifts in systems persisting with Bd following disease-induced declines. Our results show that Bd aggregation is highly conserved across disparate systems and contains signatures of potential biological processes of amphibian-Bd systems. Our work can inform future modelling approaches and be extended to other fungal pathogens to elucidate host-fungal interactions and unite host-fungal dynamics under a common theoretical framework.
Keywords: aggregation; amphibian; Batrachochytrium dendrobatidis; distribution; fungal parasites/pathogens; integral projection model